Profit Rates and Intangible Capital - Megna, Pamela; Mueller, Dennis C. (The Review of Economics and Statistics, 1991)
A central question in industrial organization is why profit rates differ so dramatically across firms and industries. One of the many explanations offered for this phenomenon is the failure of conventional accounting methods to adjust for intangible capital stocks, i.e., it is argued that profit rates do not differ dramatically when capital stocks are correctly calculated to include intangible R&D and advertising capital. To test this hypothesis individual advertising capital stocks are calculated for firms in the toys, distilled beverages, cosmetics, and pharmaceuticals industries, and R&D stocks are calculated for the pharmaceuticals firms. The adjustments do not eliminate the wide dispersion in profit rates. Copyright 1991 by MIT Press.